A Case Series: Cognitive-Behavioral Treatment (Exposure, Relaxation, and Rescripting Therapy) of Trauma-Related Nightmares Experienced by Children. (February 2013) - Fernandez, Shantel; DeMarni Cromer, Lisa; Borntrager, Cameo; Swopes, Rachael; Hanson, Rochelle F.; Davis, Joanne L.
Two case studies are presented to demonstrate that children who experience trauma-related nightmares may benefit from cognitive-behavioral therapy for this sleep problem. The treatment was adapted from the empirically supported adult treatment for chronic trauma-related nightmares: exposure, relaxation, and rescripting therapy (ERRT). Pretreatment and posttreatment nightmare frequency and severity were measured in addition to subjective nightmare-related distress, behavioral problems, sleep quality and quantity, and symptoms of posttraumatic stress disorder (PTSD), anxiety, and depression. Improvement in nightmare and sleep disturbance frequencies were found as well as reductions in parents' reports of child behavior problems. This study provides preliminary support for the use of ERRT with children.